The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1017/s003118202000092x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Pumilio domain protein PUF3 inTrypanosoma bruceigrowth and differentiation

Abstract: Trypanosomes strongly rely on post-transcriptional mechanisms to control gene expression. Several Opisthokont Pumilio domain proteins are known to suppress expression when bound to mRNAs. The Trypanosoma brucei Pumilio domain protein PUF3 is a cytosolic mRNA-binding protein that suppresses expression when tethered to a reporter mRNA. RNA-binding studies showed that PUF3 preferentially binds to mRNAs with a classical Pumilio-domain recognition motif, UGUA[U/C]AUU. RNA-interference-mediated reduction of PUF3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…S4C). This may suggest that the correct level of PUF3 is required for optimal growth and that an excess might be toxic, as was shown in the related parasite, T. brucei [ 24 ] and in S. cerevisiae [ 21 ].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S4C). This may suggest that the correct level of PUF3 is required for optimal growth and that an excess might be toxic, as was shown in the related parasite, T. brucei [ 24 ] and in S. cerevisiae [ 21 ].…”
Section: Resultsmentioning
confidence: 95%
“…Recently, the PUF3 protein was evaluated in this parasite; the study concluded that PUF3 may have a role in fine-tuning gene expression since RNA-interference PUF3 bloodstream forms had only minor growth defects, and the transcriptome was unaffected. Furthermore, procyclic forms without PUF3 grew slower, but ectopic expression of PUF3 impaired their viability, suggesting a toxic effect of the protein [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starting with the same initial total RNA samples, we made mRNA by oligo d(T) selection, or by depleting rRNA using RNase H and complementary oligonucleotides. We had previously demonstrated, by comparing with total RNA, that the latter procedure has no effect on the transcriptome [25]. Analysis of the transcriptomes clearly showed that oligo d(T) selection causes loss of longer RNAs (S1C Fig).…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 90%
“…Moreover, we observed Pumilio binding motifs at the predicted TglncRNA sequence that let us infer that the sequence would be functional 45 . Although Pumilio proteins were characterized in T. gondii and other parasites as regulators of translation by mRNA binding during differentiation processes [61][62][63] , no role at genome stability was proposed. In fact, a motif binding search for PUM proteins at T. gondii 5'-UTR and 3'-UTR transcripts reveals mRNA targets like those that codify for DNA repair proteins.…”
Section: Discussionmentioning
confidence: 99%